Screening for clinically significant non-deletional alpha thalassaemia mutations by pyrosequencing. - Haywood, A; Dreau, H; Timbs, A; Schuh, A; Old, J; Henderson, S (2010)
Non-deletional α(+)-thalassaemia is associated with a higher degree of morbidity and mortality than deletional forms of α(+)-thalassaemia. Screening for the common deletional forms of α-thalassaemia by Gap-PCR is widely practiced; however, the detection of non-deletional α-thalassaemia mutations is technically more labour-intensive and expensive, as it requires DNA sequencing. In addition, the presence of four very closely homologous alpha globin genes and the frequent co-existence of deletional forms of α-thalassaemia present another layer of complexity in the detection of these mutations. With growing evidence that non-deletional α-thalassaemia is relatively common in the UK, there is a demand for technologies which can quickly and accurately screen for these mutations. We describe a method utilising pyrosequencing for detecting the ten most common clinically significant non-deletional α-thalassaemia mutations in the UK. We tested 105 patients with non-deletional α-thalassaemia and found 100% concordance with known genotype as identified by Sanger sequencing. We found pyrosequencing to be simpler, more robust, quicker, and cheaper than conventional sequencing, making it a good choice for rapid and cost-effective diagnosis of patients with suspected non-deletional α-thalassaemia. The technique is also likely to help expedite prenatal diagnosis of pregnancies at risk of α-thalassaemia major.